Neprilysins: An Evolutionarily Conserved Family of Metalloproteases That Play Important Roles in Reproduction in Drosophila. Issue 3 (1st March 2014) - Sitnik, Jessica L; Francis, Carmen; Hens, Korneel; Huybrechts, Roger; Wolfner, Mariana F; Callaerts, Patrick
Abstract: Members of the M13 class of metalloproteases have been implicated in diseases and in reproductive fitness. Nevertheless, their physiological role remains poorly understood. To obtain a tractable model with which to analyze this protein family's function, we characterized the gene family in Drosophila melanogaster and focused on reproductive phenotypes. The D. melanogaster genome contains 24 M13 class protease homologs, some of which are orthologs of human proteases, including neprilysin. Many are expressed in the reproductive tracts of either sex. Using RNAi we individually targeted the five Nep genes most closely related to vertebrate neprilysin, Nep1-5, to investigate their roles in reproduction. A reduction in Nep1, Nep2, or Nep4 expression in females reduced egg laying. Nep1 and Nep2 are required in the CNS and the spermathecae for wild-type fecundity. Females that are null for Nep2 also show defects as hosts of sperm competition as well as an increased rate of depletion for stored sperm. Furthermore, eggs laid by Nep2 mutant females are fertilized normally, but arrest early in embryonic development. In the male, only Nep1 was required to induce normal patterns of female egg laying. Reduction in the expression of Nep2-5 in the male did not cause any dramatic effects on reproductive fitness, which suggests that these genes are either nonessential for male fertility or perform redundant functions. Our results suggest that, consistent with the functions of neprilysins in mammals, these proteins are also required for reproduction in Drosophila, opening up this model system for further functional analysis of this protein class and their substrates.